An assessment of the Egyptian government alternative healthcare coverage system: treatment at the expense of state - Radwan, Rasha Sadek (AUC Knowledge Fountain, 2013)
The Program of Treatment at the Expense of State (PTES) is the main alternative available for underprivileged Egyptian patients who cannot otherwise afford to pay for adequate medical treatment. Therefore, it is important to investigate whether or not it fulfills this role and reaches its intended beneficiaries. This research discusses the administrative as well as the financial framework of the PTES and investigates its effectiveness, efficiency and responsiveness. Although the system is openly criticized, the perceptions differ according to the roles and experiences of the different stakeholders. A number of interviews were conducted with officials in the Ministry of Health, the Specialized Medical Councils, as well as patients and doctors, in order to assess the benefits of the PTES and its deficiencies. Officials maintain that strict rules and regulations were lately implemented to insure the effectiveness and efficiency of the system. Patients acknowledge that the PTES is providing them with the medical services that they cannot otherwise afford, however, they point out to some deficiencies in the system such as the time it takes to get the approval and to renew it and the insufficient funds allocated per patient in some cases. Creative ways to increase the funds of the PTES are recommended such as fundraising campaigns and partnerships with the NGOs. Better and faster communication with the patients is recommended as well as more flexibility in dealing with severe cases.